The impact of physical exercise on adolescents’ social-emotional competence: The chain mediating role of social support and peer relationships - Qin Zeng; Pengfei Wen; Kelei Guo (PLoS ONE, 2025)
This study aims to explore the relationship between physical exercise and adolescents’ social-emotional competence, and analyze the chain mediating effects of social support and peer relationships. Data from 316 adolescents were collected through questionnaires, and measurements were conducted on four aspects: physical exercise, social support, peer relationships, and adolescents’ social-emotional competence. The results showed that physical exercise had a significant positive predictive effect on adolescents’ social-emotional competence, with social support and peer relationships playing significant mediating roles between physical exercise and adolescents’ social-emotional competence. Three specific mediating pathways were identified: (1) the independent mediating effect of social support between physical exercise and adolescents’ social-emotional competence; (2) the independent mediating effect of peer relationships between physical exercise and adolescents’ social-emotional competence; and (3) the chain mediating effect of social support and peer relationships between physical exercise and adolescents’ social-emotional competence. The findings reveal the intrinsic mechanisms through which physical exercise influences adolescents’ social-emotional competence, while also providing theoretical support and practical evidence for promoting the development of adolescents’ social-emotional competence.